1979
DOI: 10.1016/0301-5629(79)90086-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic absorption and attenuation in mammalian tissues

Abstract: Abstract--The ultrasonic absorption was determined, by the transient thermoelectric method, for brain, heart, kidney, liver, tendon, and testis from cat, mouse, pig and beef. Comparison of these absorption {a) values with published values of attenuation (A) shows: (1) that the a and A coefficients have nearly the same frequency dependencies in the range 0.5-7 MHz, (2) that the magnitudes of a and A differ appreciably and that difference depends upon the method of measurement and tissue type, and (3) that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(138 citation statements)
references
References 17 publications
5
132
1
Order By: Relevance
“…Our previous study 7 showed that the attenuation coefficient values obtained with the novel method were significantly greater than those obtained with the SS method in fatty livers, but no significant differences were seen in normal and cirrhotic livers. Many reports [16][17][18][19][20] indicate that a power law function of the type α(f ) = α 0 f n describes the frequency dependence rather well. As in most reports, a linear frequency dependence of attenuation, that is, n = 1, was assumed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study 7 showed that the attenuation coefficient values obtained with the novel method were significantly greater than those obtained with the SS method in fatty livers, but no significant differences were seen in normal and cirrhotic livers. Many reports [16][17][18][19][20] indicate that a power law function of the type α(f ) = α 0 f n describes the frequency dependence rather well. As in most reports, a linear frequency dependence of attenuation, that is, n = 1, was assumed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Reported pressure amplitudes are estimates in vivo, taking into account this loss through the skull and ultrasound attenuation in the brain, with a mean attenuation coefficient of 5 Np/m/MHz. 32 The transducer was mounted on an MR-compatible positioning system and immersed in a tank of degassed water. Each rat was placed in the supine position on the sonication table in a 3-T clinical MRI scanner.…”
Section: Ultrasoundmentioning
confidence: 99%
“…In contrast, other investigators (Goss et al 1978(Goss et al , 1979(Goss et al , 1980 showed a large range of acoustic attenuation coefficients for bone tissue. The acoustic attenuation coefficient of bone is one of the crucial factors determining the distributions of SAR ratio in tissues.…”
Section: Resultsmentioning
confidence: 75%